2013
DOI: 10.1155/2013/796290
|View full text |Cite
|
Sign up to set email alerts
|

ESR1rs9340799 Is Associated with Endometriosis-Related Infertility andIn VitroFertilization Failure

Abstract: Estrogen receptor alpha has a central role in human fertility by regulating estrogen action in all human reproductive tissues. Leukemia inhibitory factor (LIF) expression, a cytokine critical for blastocyst implantation, is mediated by estrogen signaling, so we hypothesized that ESR1 gene polymorphisms might be candidate risk markers for endometriosis-related infertility and in vitro fertilization (IVF) failure. We included 98 infertile women with endometriosis, 115 infertile women with at least one IVF failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 46 publications
3
30
0
2
Order By: Relevance
“…In contrast, Fraga et al (2014) did not observe a correlation between LIF SNP T/G (rs929271) and recurrent pregnancy loss. In the same context, Paskulin et al (2013) found no correlation between LIF SNP T/G (rs929271) and endometriosis or IVF failure. Furthermore, Tagliani-Ribeiro et al (2012) analysed the correlation between genetic polymorphism and the incidence of dizygotic and monozygotic twins, and found no difference between cases and controls in the allelic or genotypic frequencies of LIF T/G (rs929271).…”
Section: Introductionmentioning
confidence: 86%
“…In contrast, Fraga et al (2014) did not observe a correlation between LIF SNP T/G (rs929271) and recurrent pregnancy loss. In the same context, Paskulin et al (2013) found no correlation between LIF SNP T/G (rs929271) and endometriosis or IVF failure. Furthermore, Tagliani-Ribeiro et al (2012) analysed the correlation between genetic polymorphism and the incidence of dizygotic and monozygotic twins, and found no difference between cases and controls in the allelic or genotypic frequencies of LIF T/G (rs929271).…”
Section: Introductionmentioning
confidence: 86%
“…Amplification of the REα gene rs9340799 changes in nucleotide A to G using restriction enzymes XbaI in region intron 1 were reported by Paskulin et al 11 Study from NCBI showed that individuals with genotype AA normal is an individual with a lower risk of cases of endometriosis, whereas individuals with genotype GG has 10 times higher against the risk of endometriosis. The results in this experiment found the proportion of genotype GA in the case of endometriosis was more dominant than the other genotypes.…”
Section: Gene Polymorphism Analysis Reα Rs9340799 a / G Gen Reα Rs22mentioning
confidence: 99%
“…This study revealed that the genotype frequencies in control and endometriosis groups showed no difference. Amplification of the REα gene region intron 1 SNP rs2234693 T nucleotide changes into C using the restriction enzyme PvuII as reported by Paskulin et al 11 The second difference in allele frequency in both groups (endometriosis and control) conducted chi-square test. It can be concluded that the genotype frequency in endometriosis and control groups were no difference, as well as statistical tests that appeared no difference in allele frequency between the two groups of the endometriosis and the control with p = 0.422 (p> 0.05).…”
Section: Gene Polymorphism Analysis Reα Rs9340799 a / G Gen Reα Rs22mentioning
confidence: 99%
See 2 more Smart Citations